Research progress on the relationship between chronic prostatitis/chronic pelvic pain syndrome and the microbiota of the reproductive system - Song, Wei-Jie; Liu, Xin-Yi; He, Le-Ye (Frontiers in Cellular and Infection Microbiology, 2024)
Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common pelvic pain syndrome in males, seriously affecting patients' quality of life. For a long time, CP/CPPS has research directions, aiming to provide new ideas and methods for clinical diagnosis and treatment, thereby improving the treatment outcomes and quality of life of CP/CPPS patients.Keywords：chronic prostatitis/ chronic pelvic pain syndrome; reproductive system microorganisms; clinical diagnosis; treatment; research progress